POLA DISTRIBUSI POPULASI Rhizophora apiculata Blume DI HUTAN MANGROVE PANTAI BILIK TAMAN NASIONAL BALURAN - Nur Endah Novia Lestari; Sudarmadji Sudarmadji; Retno Wimbaningrum (Lambung Mangkurat University-Indonesia, 2019)
Bilik beach Baluran National Park (TNB) is dominated by mangrove forest and one type of mangrove found was Rhizophora apiculata Blume. So far there has been no information about the distribution pattern of R. apiculata Blume in mangrove forest of Bilik beach TNB. This distribution pattern is very needed as a source of information in the managing and preserving the mangrove forest conservation areas. The method was done by collecting data of R. apiculata Blume and the abiotic environmental factors. It was done in 10x10 m2 plot. The data of R. apiculata Blume that has been recorded included the number of trees, circumference of the stem, position of tree coordinates, and some parts of the R. apiculata Blume plant. The data were analyzed using the the Standardized Morisita Index value and ArcGIS 10.1 software. . There has been found 147 trees that control a space of 3.19 m2 in the area of 10.600 m2. The distribution pattern of R. apiculata Blume in coastal mangrove forests in Bilik TNB grouped based on the value of the Standard Morisita Index (Ip) which is more than zero. It is supported by the spatial map obtained from the ArcGIS 10.1 digitization that shows 66,6 % of R. apiculata Blume presence grows close to one and another. The clustered distribution pattern is caused by the stilt-root characteristics and morphological structure of the reproductive organs R. apiculata Blume.